Synthesis of uranium trichloride salt using ZnCl2 - Kim, Gha-Young; Kim, Tack-Jin; Jang, Junhyuk; Eun, Hee-Chul; Lee, Sung-Jai (Journal of radioanalytical and nuclear chemistry, 2018)
We report a method for preparing uranium trichloride, UCl 3 , by reacting ZnCl 2 with U in a molten LiCl–KCl eutectic salt at 500 °C. Cyclic voltammetry indicated the formation of UCl 3 as the reaction proceeded. After 30 h, the reaction was terminated and the final product was confirmed to contain 13.2 wt% UCl 3 –LiCl–KCl salt by the ICP-OES method.